Differentiating the Impacts of Cu2O Initial Low‐ and High‐Index Facets on Their Reconstruction and Catalytic Performance in Electrochemical CO2 Reduction Reaction. (1st January 2023) - Han, Chen; Kundi, Varun; Ma, Zhipeng; Toe, Cui Ying; Kumar, Priyank; Tsounis, Constantine; Jiang, Junjie; Xi, Shibo; Han, Zhaojun; Lu, Xunyu; Amal, Rose; Pan, Jian
Abstract: Oxide‐derived Cu catalysts from Cu2 O microcrystals are capable of electrochemically converting CO2 into various value‐added chemicals. However, their structural transformation and associated preferred products remain unclear, requiring further investigation. Herein, Cu2 O microcrystals with controllable low‐ and high‐index facets exposure are fabricated to differentiate the effects of initial exposed facets on their structural reconstruction and product selectivity in electrochemical CO2 reduction reaction. Combined in situ characterizations and theoretical investigation reveal the direct correlations of Cu2 O reconstruction and product selectivity to its initial facet exposure. The Cu2 O low‐index facet, being more stable with a high energy barrier on material reduction, tends to partially maintain its original crystalline structure and larger Cu2 O particle size throughout the transformation. The derived flatter surface and limited Cu2 O/Cu interfaces result in a favorable selectivity toward 2‐electron transfer products. The chemically active Cu2 O high‐index facet (311) is energetically favorable to be reduced owing to the feasible protonation process, thus experiencing a drastic reconstruction with rich newly formed Cu nanoparticles and evolved fine Cu2 O grains; Such a reconstruction creates uncoordinated Cu species and abundant boundaries, benefiting charge transfer and increasing the local pH by confining OH −, thus leading to a high selectivity toward C2+ products. Abstract : This study, for the first time, reveals that the initial facet exposure of Cu2 O directly determines its transformation under electrochemical CO2 reduction reaction conditions, which subsequently governs the catalytic activity and product selectivity. The operando synchrotron radiation powder diffraction is used together with in situ Raman to systematically differentiate the impacts of Cu2 O initial low‐ and high‐ index facets on their reconstruction and catalytic performance, giving a clear structure‐performance relationship.